Gender Discrimination in the Labor Market - Schaffer, David L.; Westenberg, Joseph M.; Soborowicz, Levi (My University, 2018)
In recent research, some economists have suggested that most of the remaining gap in wages between men and women in the U.S. can be explained by the fact that women have more family obligations than men, especially for childcare and eldercare, and therefore choose more flexible jobs. However, these jobs pay less than other similar jobs because workers are less productive in jobs with greater flexibility. So, women are voluntarily staying in these lower-paying jobs. Their overall lower pay is not caused by any type of gender discrimination. In this view, there may be no further need for equal pay and affirmative action public policies in regards to gender. We address one major question: does the data support this new contention? We analyze the data using a variety of statistical techniques, and find only weak support for this theory.
Color poster with text, graphs, and tables.
Keywords: Gender wage gap; Wages--United States--Social aspects; Wages--United States--Sex differences; Gender discrimination; Posters